2020
DOI: 10.1101/2020.10.15.20213512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 neutralizing antibodies predict disease severity and survival

Abstract: COVID-19 exhibits variable symptom severity ranging from asymptomatic to life-threatening, yet the relationship between severity and the humoral immune response is poorly understood. We examined antibody responses in 113 COVID-19 patients and found that severe cases resulting in intubation or death exhibited increased inflammatory markers, lymphopenia, and high anti-RBD antibody levels. While anti-RBD IgG levels generally correlated with neutralization titer, quantitation of neutralization potency revealed tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 65 publications
5
44
0
Order By: Relevance
“…The cohort consists primarily (91.69%) of patients with mild COVID-19 therefore representing the predominant clinical course of this disease 6 . Since higher disease severity was shown to correlate with higher antibody responses 14,42 , cohorts mainly composed of hospitalized individuals have limited applicability on the majority of COVID-19 cases 20,35,43,44 . Moreover, to our knowledge this is the most comprehensive study (n=963), in which neutralizing antibody activity has been reported to date with the next largest study having analyzed 4-5 fold less individuals at a single time point 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The cohort consists primarily (91.69%) of patients with mild COVID-19 therefore representing the predominant clinical course of this disease 6 . Since higher disease severity was shown to correlate with higher antibody responses 14,42 , cohorts mainly composed of hospitalized individuals have limited applicability on the majority of COVID-19 cases 20,35,43,44 . Moreover, to our knowledge this is the most comprehensive study (n=963), in which neutralizing antibody activity has been reported to date with the next largest study having analyzed 4-5 fold less individuals at a single time point 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The D614G mutation causes an allosteric change in the spike RBD (61,62), and exhibits efficient replication in vitro and transmission in animal models (63,64); however there are no indications thus far of higher clinical severity or mortality (65). Additionally, D614G mutant pseudovirus is neutralized by both convalescent patient sera and vaccine-elicited immune sera (66,67). Minkassociated variants are not associated with rapid spread or increased disease severity among humans, and preliminary serology assessments show that convalescent sera with varying antibody titers neutralize both wildtype and mink-variant virus suggesting that it is unlikely that these mutations will jeopardize the effects of vaccines or therapeutics (68,69).…”
Section: Breadth Of Immune Coverage Of Emerging Sars-cov-2 Variantsmentioning
confidence: 99%
“…Potent neutralizing antibodies against SARS-CoV-2 appear to increase survival and may protect against reinfection with variants of SARS-CoV-2. In a cohort of 113 patients infected with SARS-CoV-2 stratified by disease severity and outcomes (i.e., non-hospitalized, hospitalized, intubated, immunosuppressed, and deceased), anti-RBD antibody levels, neutralization titers, and neutralization potency indices predicted disease severity and survival (66). Comprehensive immunophenotyping of peripheral blood in 42 individuals with divergent clinical trajectories of SARS-CoV-2 infection and COVID-19 (moderate n = 7, severe n = 28, recovered n = 7) showed perturbations in multiple leukocyte populations, which distinguished cases of severe COVID-19 from healthy donors, cases of moderate COVID-19, and from patients who have recovered from COVID-19 (44).…”
Section: Systems Serology and Systems Immunologymentioning
confidence: 99%
“…The cohort consists primarily (91.69%) of patients with mild COVID-19 therefore representing the predominant clinical course of this disease 6 . Since higher disease severity was shown to correlate with higher antibody responses 14,42 , cohorts mainly composed of hospitalized individuals have limited applicability on the majority of COVID-19 cases 20,35,43,44 . Moreover, to our knowledge this is the most comprehensive study (n = 963), in which neutralizing antibody activity has been reported to date with the next largest study having analyzed 4-5 fold less individuals at a single time point 45 The broad spectrum of neutralizing activity developed in COVID-19 recovered individuals may impact the level of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…NAb response presented here is comparable to recent spike-based mRNA vaccine studies in age group 18-55, where geometric mean neutralizing titers were in the range of 100-300 ID 50 (depending on dose) 1.5 months post vaccination 17,50 versus 111.3 ID 50 in this study. Recent studies have reported that age, gender and disease severity 14,36,44 can impact SARS-CoV-2 NAb titers 14,36,42,43,45 . However, a comprehensive analysis on a large representative cohort was missing.…”
Section: Discussionmentioning
confidence: 99%